2015
DOI: 10.1111/tmi.12530
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of anaemia among African migrants in Germany persists after exclusion of iron deficiency and erythrocyte polymorphisms

Abstract: Abstractobjectives Haematological parameters differ between individuals of African and European ancestry. However, respective data of first-generation African migrants are virtually absent. We assessed these in Ghanaian migrants living in Berlin, compared them with reference data from Germany and Ghana, and estimated the role of iron deficiency (ID) and erythrocyte polymorphisms in anaemia.methods A total of 576 Ghanaians (median age, 45 years) were analysed. Blood counts were performed, haemoglobinopathies an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
6
0
1
Order By: Relevance
“…Although a previous study on the Cambodian population found that G6PDd was associated with lower hemoglobin levels (33) , we could discern no clear relationship between G6PDd and hemoglobin levels in the present study. However, in another study, Satyagraha et al (34) found that G6PDd was associated with higher hemoglobin levels, whereas, in contrast, other studies have found no correlation between G6PDd and hemoglobin levels (35) (36) .…”
Section: Discussionmentioning
confidence: 80%
“…Although a previous study on the Cambodian population found that G6PDd was associated with lower hemoglobin levels (33) , we could discern no clear relationship between G6PDd and hemoglobin levels in the present study. However, in another study, Satyagraha et al (34) found that G6PDd was associated with higher hemoglobin levels, whereas, in contrast, other studies have found no correlation between G6PDd and hemoglobin levels (35) (36) .…”
Section: Discussionmentioning
confidence: 80%
“…This is in line with the high prevalence of iron deficiency among black Africans including Ghanaians. A prevalence of 32.0% was reported among Ghanaian women living in Germany [ 19 ], 41–63% iron deficiency among Ivoirians women [ 20 ], and 39% IDA among Nigerians women aged 16–45 years [ 21 ]. Thalassaemia is equally prevalent in Ghanaians, alpha-thalassaemia is about 34% [ 19 ] and beta-thalassaemia is about 5% [ 22 ], but could not be differentiated due to restriction on confirmatory investigations at the selected centres.…”
Section: Discussionmentioning
confidence: 99%
“…One fifth of patients had no cause for anaemia documented in their notes either before transfusion or during their admission. Over 40% of transfused patients had microcytic anaemia which in Ghana would most commonly be due to iron deficiency anaemia or a haemoglobinopathy . Only a limited number of investigations to determine the cause of anaemia are available at VRH and patients may not be able to afford investigations.…”
Section: Discussionmentioning
confidence: 99%